EVALUASI TINGKAT KEPUASAN PENGGUNA TERHADAP SISTEM INFORMASI WEB TEKNIK.UMPO.AC.ID MENGGUNAKAN METODE EUCS - Vandu Yogi Saputra; Dwiyono Ariyadi; Aslan Alwi (KOMPUTEK, 2019)
The existence of an information system can make it easier to provide information and services. The Faculty of Engineering of Muhammadiyah University Ponorogo itself has an information system in the form of a website which is used almost every day by students. teknik.umpo.ac.id is a web address that is owned by the faculty of engineering, sometimes students have a lot of complaints about the information and services provided in it, whether the information is less up to date or even the appearance is a bit confusing when opened via a smartphone. The author aims to evaluate the information system to improve services to students. One method for measuring satisfaction is EUCS or End User Computing Satisfaction. Content variable in Content value gets 42.5% percentage which is included in the category of Disagree, Accuracy (Accuracy) of 62.6% percentage of which is in the category of Agree, Display (Format) with 65.73% of the percentage that is included in the Agree category . Ease of Use (user convenience) with a percentage of 77% included in the Agree category. On time (Timeliness) with a percentage rate of 29% which is included in the category of Disagree. The dominant factor in creating user satisfaction in the EUCS method on the technical website.umpo.ac.id is the variable that has the highest mean (mean), namely the ease of use variable which reaches a value of 77%, while the variable which has the lowest mean (mean), which is the Timeliness variable with a percentage of 29%.